Three for one - Cardiac perforations at three sites following atrial septal defect device closure - Ravi Agarwal; Sowmya Srinivasan (Wolters Kluwer Medknow Publications, 2024)
The interventional cardiac catheterization for treating congenital heart disease has evolved. Complications following interventional procedures might need emergency surgery as a bailout. Here, we report a case of cardiac perforations in three different sites following device closure of atrial septal defect (ASD). In literature, the major sites of ASD device erosion are at the roof of the right atrium (RA), left atrium (LA), or at the atrial junction with the aorta. In our patient, the device eroded at all three sites: the roof of the LA, RA, and the aorta, causing hemopericardium.